2021
DOI: 10.1186/s42269-021-00600-3
|View full text |Cite
|
Sign up to set email alerts
|

Human identification from washed blood stains

Abstract: Background Among the physical evidence, bloodstain is one of the most common biological pieces of evidence at the crime scene, especially in violent crimes. Bloodstains are frequently seen at the crime scene and can be easily detected due to their color and structure. Because blood and bloodstains can potentially be evidence of a crime, offenders often tend to clean or wash them to get rid of relevant evidence. Some researchers think that washed bloodstains cannot obtain enough quality DNA for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Visualization of blood stains after washing can also be difficult [ 158 , 159 ]. Kulstein and Wiegand [ 160 ] confirmed, however, that despite washing blood-stained clothes at 40 °C and 60 °C, it is possible to obtain a full STR profile from the sampled material [ 161 ]. Obtaining a high-quality DNA profile was also confirmed for fabrics washed at 90 °C by Alice et al [ 152 ].…”
Section: Degradation Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Visualization of blood stains after washing can also be difficult [ 158 , 159 ]. Kulstein and Wiegand [ 160 ] confirmed, however, that despite washing blood-stained clothes at 40 °C and 60 °C, it is possible to obtain a full STR profile from the sampled material [ 161 ]. Obtaining a high-quality DNA profile was also confirmed for fabrics washed at 90 °C by Alice et al [ 152 ].…”
Section: Degradation Factorsmentioning
confidence: 99%
“…Obtaining a high-quality DNA profile was also confirmed for fabrics washed at 90 °C by Alice et al [ 152 ]. However, the results of Ünsal et al [ 161 ] contradicted the results, as they reported obtaining a complete genetic profile only from fabrics washed at 40 °C and 60 °C [ 161 ].…”
Section: Degradation Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In certain poisoning cases, the cause of death may be established from the chemical analysis of the blood. 4,5 Time since death may be estimated from the biochemical and enzyme changes in the blood. However, we must take care because false criminal charges may be brought by using animals or other blood-like substances.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, advancements in technology have elevated the significance of DNA profiles as crucial evidence in criminal investigations, offering individualization capabilities. Consequently, the analysis of biological materials derived from crime scenes has gained heightened importance, and efforts to enhance this analysis are ongoing (Ünsal Sapan, Erdoğan and Atasoy, 2021).…”
Section: Introductionmentioning
confidence: 99%